HEAT TRANSFER ANALYSIS OF DOUBLE TUBE HEAT EXCHANGER WITH WAVY INNER TUBE - Hasgul, Ceren; Cakmak, Gulsah (Vinca Inst Nuclear Sci, 2022)
The effect of the design on the heat transfer is numerically investigated by using the wavy inner tube in a double-pipe heat exchanger. A wavy inner tube was used in the design to give a turbulent effect to the fluid along the inner tube of a double tube heat exchanger. In numerical study, ANSYS 12.0 Fluent code program was used, and the basic protection equations were solved for steady-state, 3-D and turbulent flow conditions. The study was examined at Reynolds numbers ranging from 2700-5300. The obtained results were compared with the experimental data performed under the same conditions. As a result of this comparison, after it was seen that the results obtained from the numerical analysis and the experimental results were compatible with each other, the wave number of the inner tube was increased and analyzed with the ANSYS fluent code program. When the data obtained as a result of the analyzes were evaluated, it was seen that the highest heat transfer was obtained from the 16 wave tube heat exchanger, which has the highest number of waves and under counter flow conditions. The increase in heat transfer increased by 270% compared to the straight tube.
Keywords: double tube heat exchanger; wavy inner tube; finite volume method